Macrophage-Specific Connexin 43 Knockout Protects Mice from Obesity-Induced Inflammation and Metabolic Dysfunction - Choi, Cheoljun; Saha, Abhirup; An, Seungchan; Cho, Yoon Keun; Kim, Heeseong; Noh, Minsoo; Lee, Yun-Hee (Frontiers in Cell and Developmental Biology, 2022)
Adipose tissue macrophages are a major immune cell type contributing to homeostatic maintenance and pathological adipose tissue remodeling. However, the mechanisms underlying macrophage recruitment and polarization in adipose tissue during obesity remain poorly understood. Previous studies have suggested that the gap junctional protein, connexin43 (Cx43), plays a critical role in macrophage activation and phagocytosis. Herein, we investigated the macrophage-specific roles of Cx43 in high-fat diet (HFD)-induced pathological remodeling of adipose tissue. Expression levels of Cx43 were upregulated in macrophages co-cultured with dying adipocytes in vitro, as well as in macrophages associated with dying adipocytes in the adipose tissue of HFD-fed mice. Cx43 knockdown reduced lipopolysaccharide (LPS)-induced ATP release from macrophages and decreased inflammatory responses of macrophages co-cultured with dying adipocytes. Based on global gene expression profiling, macrophage-specific Cx43-knockout (Cx43-MKO) mice were resistant to HFD-induced inflammatory responses in adipose tissue, potentially via P2X7-mediated signaling pathways. Cx43-MKO mice exhibited reduced HFD-induced macrophage recruitment in adipose tissue. Moreover, Cx43-MKO mice showed reduced inflammasome activation in adipose tissues and improved glucose tolerance. Collectively, these findings demonstrate that Cx43 expression in macrophages facilitates inflammasome activation, which, in turn, contributes to HFD-induced metabolic dysfunction.